PackMerger: A 3D Print Volume Optimizer. (26th May 2014) - Vanek, J.; Galicia, J. A. Garcia; Benes, B.; Měch, R.; Carr, N.; Stava, O.; Miller, G. S.
<x xml:space="preserve">Abstract</x> We propose an optimization framework for 3D printing that seeks to save printing time and the support material required to print 3D shapes. 3D printing technology is rapidly maturing and may revolutionize how we manufacture objects. The total cost of printing, however, is governed by numerous factors which include not only the price of the printer but also the amount of material and time to fabricate the shape. Our PackMerger framework converts the input 3D watertight mesh into a shell by hollowing its inner parts. The shell is then divided into segments. The pieces are then tightly packed using optimization. The optimization attempts to minimize the amount of support material and the bounding box volume of the packed segments. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>